REPRESENTASI ETNIS TIONGHOA DALAM FILM NGENEST - Novaltri Sarelpa Cerba; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The process of interpreting ideas, knowledge, or messages is physically called representation. Representation refers to both the process and events of the meaning of a sign. Chinese ethnicity in Indonesia is a minority, with ethnicity having a history that is not good in the eyes of Indonesians. Problems that occur in Chinese ethnic have been raised and constructed through mass media, such as through film. The issue of Chinese ethnicity that is displayed in a film becomes an interesting story, through the film the problems that occur in the Chinese ethnic can be displayed and reconstructed so that they can be witnessed by a large audience. The world of cinema in Indonesia was again presented by a comedy drama film made by Starvision Plus, titled NGENEST, which brought up stories about ethnic Chinese in Indonesian society. Therefore, this study aims to find out how the representation of the ethnic Chinese in the NGENEST film. This study uses a type of qualitative research with Roland Barthes's semiotic analysis. The research subjects are the scenes in the NGENEST film. The objects in this study are NGENEST audio and visual films. In this study using Observation Data Collection, Documentation and Library Studies Techniques. To achieve the validity of the data in this study the authors used Triangulation Based on the results of the study using the Roland Semiotics analysis and Chinese ethnic culture, Chinese Ethnic Representations in the NGENEST film showed that the opinion of the general public about the characteristics of Chinese ethnicity who had slanted white eyes, showed that they were the majority, causing problems and they get bad treatment, this makes some Chinese ethnic reluctant to blend so that the ethnocentric attitude that is in accordance with Chinese mentality based on Kong Fu Tse's teachings has arisen. Chinese ethnics in Indonesia are divided into two: totok and pranakan, wherein the Chinese are ethnic Chinese who have mingled with culture or life in Indonesia, it appears that they use Indonesian in their daily lives and have beliefs besides the traditional beliefs of ethnic Tionghoa. And the Chinese ethnic community is also considered by the people who like to trade, this is because Chinese people live by trading or entrepreneurship in fulfilling their daily needs or as their livelihood Keywords: Representation, Semiotics, Ethnicity, Chinese